DERIVATIONAL MORPHOLOGY USED IN A SHORT STORY OF JOHN ROSSITER’S WIFE - Febriyanti, Febriyanti; Hajjah Zulianti (ELTIN Journal, 2024)
The purpose of this study is to analyze types of derivational morphology found in the short story entitled "John Rossiter's Wife". In addition, this research also finds out which type or group of derivational morphology is most often used in the short story. This research is descriptive qualitative research. The researchers used document analysis to collect the data. Content analysis was used to find out the group of derivational morphology in the short story. To check the quality of the data, the researchers used peer review or peer debriefing, multiple investigators, and theories. The results showed that there are 26 words from four types of derivational morphology, namely adverbs formed from adjectives, nouns formed from members of other word classes, adjectives formed from adjectives, and adjectives formed from members of other word classes. Furthermore, the result of this research revealed that the highest percentage of occurrence is adjectives derived from members of other word classes. Theoretically, this research has implications for the development of scientific insights about morphology especially derivational morphology, practically it gives implication to the readers especially EFL students and teacher in understanding and analyzing English words.